Comparative proteomics and correlated signaling network of kidney in ApoE deficient mouse. Issue 11 (31st October 2013) - Lv, Xiaoyan; Ai, Jianzhong; Li, Mi; Wang, Honglian; Chen, Tielin; Fang, Yin; Liu, Yunhong; Zhou, Puhui; Chen, Mianzhi; Tan, Ruizhi; Liu, Yuhang; Yang, Yang; et al.
<x xml:space="preserve">Abstract</x> Purpose Apolipoprotein E knockout (apoE−/−) mouse is one of the most popular models for cardiovascular research, especially in the study of atherosclerosis. Naturally, large amount of studies try to uncover the role of apoE in atherosclerosis, and indeed apoE plays an important role in this pathogenesis. Kidney is an organ that contains lots of capillaries and also largely expresses apoE. Moreover, a protective role of apoE in kidney as an autocrine regulator has been demonstrated previously, however, the underlying mechanism is largely unknown. Experimental design In this study, comparative proteomics is for the first time used to identify the differential proteins in kidneys of apoE−/− and wild type mice, respectively, and we try to reveal the signaling network of apoE in mice kidney using bioinformatics analysis. Results Our findings show that approximately 80 proteins are significantly differentially expressed in kidneys of apoE−/− and wild type mice, and the signaling network correlated to apoE is successfully established by employing bioinformatics assay. Conclusions and clinical relevance Taken together, we originally identify the proteins with differential expression and propose an apoE correlated molecular network in mice kidney. These findings further provide evidence of the role of apoE in mice kidney and a brand new perspective in the protection and treatment of kidney disease.